The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ehf2.13736
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognostic value of vasodilator stress cardiac magnetic resonance in patients with atrial fibrillation

Abstract: Aims Although the prevalence of coronary artery disease (CAD) is high among patients with atrial fibrillation (AF), studies on stress perfusion cardiac magnetic resonance (CMR) imaging frequently exclude patients with AF, and its prognostic and diagnostic value in high‐risk patients with suspected or known CAD remains unclear. Methods and results In this longitudinal cohort study, we included 164 consecutive patients with AF during vasodilator perfusion CMR. Diagnostic value was evaluated regarding invasive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…In another retrospective study with a similar cohort but a longer follow-up, Weiss et al found patients with both ischemia and LGE had the highest cumulative rate of MACEs versus ischemia or LGE only [78]. However, whether patients with AF and imaging evidence of ischemia will benefit from coronary revascularisation is unclear [79].…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…In another retrospective study with a similar cohort but a longer follow-up, Weiss et al found patients with both ischemia and LGE had the highest cumulative rate of MACEs versus ischemia or LGE only [78]. However, whether patients with AF and imaging evidence of ischemia will benefit from coronary revascularisation is unclear [79].…”
Section: Atrial Fibrillationmentioning
confidence: 99%